2008
DOI: 10.1111/j.1365-2710.2008.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of piroxicam-beta-cyclodextrin sachets on abnormal postural sway in patients with chronic low back pain

Abstract: Piroxicam-beta-cyclodextrin (PBC) sachet may have greater improvement in the treatment of chronic LBP and possess the extended effects on postural abnormality relevant to chronic LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…The protocol for sway platform testing was the same as before [5,6,8]. In brief, subjects were asked to stand motionless on a ground level platform for 60 seconds with bare feet, first with their eyes open and again with their eyes closed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol for sway platform testing was the same as before [5,6,8]. In brief, subjects were asked to stand motionless on a ground level platform for 60 seconds with bare feet, first with their eyes open and again with their eyes closed.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical assessment of sway is the single best predictor of static posture stability, which is eligible for quantitative measurement in many situations, such as LBP, spina bifida occulta, or ethanol exposure [5,6,8,9,28].…”
Section: Measurements Of Postural Swaymentioning
confidence: 99%
“…PBCD was regarded as an effective analgesic at doses of 20 and 40 mg/day. Preemptive administration of PBCD effectively reduced morphine consumption, and especially the 40-mg dose was found to be more effective than the 20-mg dose and than the treatment administered to the control group during the postoperative period (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 95%
“…No reports were identified in the literature in PubMed, from 1990 to 2009, on the use of PBCD for postoperative analgesia after endoscopic sinus surgery, although it has been shown to be effective in reducing pain in other situations (11)(12)(13)(14)(15)(16)(17)(18). NSAIDs are gaining popularity in the management of pain associated with ambulatory surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently various studies involving inclusion complexation phenomena have been reported for new generation NSAIDs which are almost insoluble in water, primarily to enhance the oral bioavailability and dissolution behavior [7][8][9]. EDC((RS)-2-(1,8-Diethyl-4,9-dihydro-3H-pyrano [3,4-b]indol-1-yl)acetic acid) is a newer NSAID belonging to the arylalkanoic class, which…”
Section: Introductionmentioning
confidence: 99%